A heart adrift [large type] - Frantz, Laura (Thorndike Press large print Christian romance series., 2022)
"It is 1755, and the threat of war with France looms over colonial York, Virginia. Chocolatier Esmée Shaw is fighting her own battle of the heart. Having reached her twenty-eighth birthday, she is reconciled to life alone after a decade-old failed love affair from which she's never quite recovered. But she longs to find something worthwhile to do with her life.Captain Henri Lennox has returned to port after a lengthy absence, intent on completing the lighthouse in the dangerous Chesapeake Bay, a dream he once shared with Esmée. But when the colonial government asks him to lead a secret naval expedition against the French, his future is plunged into uncertainty.Will a war and a cache of regrets keep them apart, or can their shared vision and dedication to the colonial cause heal the wounds of the past? Bestselling and award-winning author Laura Frantz whisks you away to a time fraught with peril--on the sea and in the heart--in this redemptive, romantic story"--